2018
DOI: 10.1039/c7ee03509h
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Aryl Sulfonimide Tagged (FAST) salts: modular synthesis and structure–property relationships for battery applications

Abstract: Fluorinated Aryl Sulfonimide Tag (FAST) anions provide a new class of modular salts with tunable properties for potential battery applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 51 publications
2
36
0
Order By: Relevance
“… 97 The same concept can also help with the preselection of ions from an already available platform, such as the fluorinated aryl sulfonimide tagged anions. 98 …”
Section: Resultsmentioning
confidence: 99%
“… 97 The same concept can also help with the preselection of ions from an already available platform, such as the fluorinated aryl sulfonimide tagged anions. 98 …”
Section: Resultsmentioning
confidence: 99%
“…21 However, the utility of these compounds as chemically and electrochemically stable electrolyte components in aprotic Li-O 2 batteries has not, to our knowledge, been examined. Guided by a comprehensive stability framework for organic molecules in the Li-O 2 oxygen electrode environment and the structure-stability relationships obtained from our previous works, 16,22 we designed the structures of these electrolyte components to be devoid of (1) vulnerable C-H bonds for hydrogen and proton removal, (2) electrophilic centers susceptible to nucleophilic substitution, and (3) highly electron-donating functional groups vulnerable to electrochemical oxidation. In this study, these three compounds were shown both experimentally and computationally (Figure S1) to exhibit exceptional stability toward a variety of harsh conditions encountered in the Li-O 2 cathode environment.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical stabilities of BTMSA, DMCF 3 SA, and BMCF 3 SA were evaluated under conditions mimicking the oxygen electrode of aprotic Li-O 2 batteries according to a previously established protocol. 16,22 These electrolyte components were combined with 0.5 equiv lithium peroxide (Li 2 O 2 ) and KO 2 powders, and the resulting mixtures were stirred at 80 C for 3 days. The lack of appreciable change in the 1 H NMR spectra collected before and after the exposure to Li 2 O 2 and KO 2 (Figures 3A-3C) indicate that these compounds are highly resistant to chemical degradation by peroxide and superoxide, in good agreement with our computational analyses (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…[ 16,17 ] Specifically, ion conductivity of composite SSEs can be improved by using a suitable lithium salt with both high oxidation stability and high dissociation degree. [ 12 ] In addition, oligomer polymers, including poly(ethylene glycol) (PEO)‐based polymers, [ 15 ] ethylene carbonates, [ 18 ] propylene carbonates [ 14 ] among others, have been added in the matrix of the composite SSEs as the plasticizer. The added plasticizer can decrease the crystallinity of PEO and the activation barrier of ion migration, thus increasing ion mobility.…”
Section: Introductionmentioning
confidence: 99%